Impact of Demographic Variables on the Work Life Balance of Married Working Women Employed in Professional and Non-Professional Jobs in Bangalore - Jose, Josphine; D. Mello, Laveena (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Women constitute 20% of the Indian work force [1]. Even though women are actively and increasingly participating in the workforce today and contributing significantly to the income of the household and the economy, their role as the center and primary care given of the family remains intact. They are expected to meticulously execute their traditional household care-giving responsibilities .This mostly leaves no space or scope for personal time or growth leading to many imbalances and dissatisfactions. The most majorly impacted aspect being their Work Life Balance. There have been studies done on work-life balance amongst IT professionals but there has been little effort made to understand the nature of challenges faced by other professional and nonprofessional working women. This study was undertaken to investigate the so far unexplored problems faced by married working women employed in professional and non – professional sectors in Bangalore in maintaining their Work Life Balance. This study considers variables like the size of the family, the age of children, work hours and the level of social support. The study specifically aims at exploring the role of technology and access to help as an enabler to improving and maintaining Work Life Balance. Do these variables help the working women in Bangalore employed in the professional and non-professional sectors to balance their personal and professional lives? The study found that variables like size of the family, the age of children, the work hours and the level of social support, do impact the stress level faced by working women.